Synthesis of activated carbon from aguaje seeds (Mauritia flexuosa) for the adsorption of the N,N-dimethylamine - Beltran-Suito, R (2015)
The authors acknowledge the financial support provided by Pontifical Catholic University of Peru (PUCP) by the Project DGI-2013-0016 and the Peruvian Council of Science (CONCYTEC) by the Project 401-2012-CONCYTEC-OAJ.